Improving Science Learning Outcomes About Material Through the Problem Based Learning Learning Model in Online Learning - Diyana CD (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research was carried out with the aim of improving student learning outcomes in science subjects about material using the Problem Based Learning model for fifth grade students at SD Negeri Limbangan 01, Losari District, Brebes Regency, for the 2019/2020 academic year with a total of 11 students.The research shows an increase in the percentage of learning outcomes, this can be seen from the KKM completeness of students from pre-cycle activities, first cycles, and second cycles. The average value of students in the initial conditions (pre-cycle) is 53.64 with classical completeness of 45%. Cycle I was 67.27 with classical completeness of 73%. Cycle II was 83.64 with 91% classical completeness. Thus, it can be concluded that the use of Problem Based Learning (PBL) in online learning can improve student learning outcomes in learning science about material